The Great Sand Fracas of Ames County : A Novel - Apps, Jerold W., 1934- (Book collections on Project MUSE., 2014)
"When the Alstage Mining Company proposes a frac sand mine in the small Ames County village of Link Lake, events quickly escalate to a crisis. Business leader Marilyn Jones of the Link Lake Economic Development Council heads the promine forces, citing needed jobs and income for the county. Octogenarian Emily Higgins and other Link Lake Historical Society members are aghast at the proposed mine location in the community park, where a huge and ancient bur oak--the historic Trail Marker Oak--has stood since it pointed the way along an old Menominee trail. Reluctantly caught in the middle of the fray is Ambrose Adler, a reclusive, retired farmer with a secret. Soon the fracas over frac sand attracts some national attention, including that of Stony Field, the pen name of a nationally syndicated columnist. Will the village board vote to solve their budget problems with a cut of the mining profits? Will the mine create real jobs for local folks? Will Stony Field come to the village to lead protests against the mine? And will defenders of the Trail Marker Oak literally draw a battle line in the sand?"--